SEE, THINK, WONDER: VIEWING SKILLS STRATEGY FOR JUNIOR HIGH SCHOOL STUDENTS - Setianingsih, Beny Arum (SEAQIL Journal of Language Education, 2025)
Students' weak critical thinking skills cause low literacy skills. With the growth of technology, literacy skills now include not only reading but also writing, speaking, listening, viewing, understanding, and presenting information in dai-ly life. This study aims to describe the concept of See, Think, Wonder thinking routines and the stages of implementing the routines to train junior high school students' viewing skills in English subjects within Merdeka Curriculum (Ku-rikulum Merdeka). A descriptive research method with Miles and Huberman’s (2014) analytical framework was applied. The results showed that the See, Think, Wonder thinking routine encourages students to make careful observa-tions and thoughtful interpretations. By fostering curiosity and critical think-ing, the routine helps students move beyond surface-level observations to gen-erate more meaningful insights and interpretations. The implementation stages of See Think Wonder thinking routines in English subjects include analyzing Learning Outcomes (Capaian Pembelajaran), formulating Learning Objectives (Tujuan Pembelajaran/TP), and compiling Learning Objective Flow (Alur Tujuan Pembelajaran/ATP), preparing Teaching Modules (Modul Ajar/MA). The process of See, Thinking, Wonder thinking routines implementation involves pre-implementation, implementation, and post-implementation stages. To op-timize results, students should engage in reading activities both at school and at home.